Unraveling Political Islam in Indonesia: A Comparative Literature Analysis - Delmus Puneri Salim (Potret Pemikiran, 2023)
Indonesia’s direct elections has increased engagement of religion in politics since the early 2000s. Moreover, some political parties have used Islam as their ideology. However, people disagree about how far does Islam engage in politics. Some believe Islam is a completed way of life including political life. Other make assertions that Muslims have to choose leaders based on their religions. Other oppose and argue that Islam has been politicized in gaining and maintaining power. Some propose separation of religion and politics. This paper aims at defining features of political Islam. Collected data was conducted by document study to texts of literature. This study reveals the features of politics and Islam are constructed within three dimensions, which are perspectives, ethics, and goals. The analysis reveals the distinction between the correct and incorrect political Islam is centered on whether its’ goals are an increase in submission to God or power in the first place. For example, the correct political Islam does not change its narratives with or without general elections in Indonesia.